Pengembangan Media Pembelajaran Berbasis Augmented Reality pada Materi Pengenalan Perangkat Lunak Kelas VIII di SMP Negeri 4 Singkawang - Ferry Marlianto; Dini Oktarika; Bagus Rasyid; Ray Fajar Friandi; Adrian Mardinata; Desvian Ananto Putra; Egi saputra (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The objective of this study is to create augmented reality educational tools for teaching software introduction topics at Singkawang 4 State Middle School. Evaluating the viability and user reception of educational content delivered through augmented reality technology. Methods of data collection involving interviews and questionnaires. The data analysis technique employs descriptive statistics. The ADDIE paradigm is employed in the research and development process. This learning media is developed through a sequential process consisting of five stages: analysis, design, development, implementation, and evaluation. The participants in this study were eighth-grade students from Singkawang 4 State Middle School. The product feasibility testing step was conducted by a pair of media specialists and one material specialist. The research findings indicated that the feasibility evaluation conducted by media specialists obtained a score of 155 out of a total possible score of 168, placing it in the “very feasible” category. The examination conducted by material experts achieved a score of 71 out of a possible 80, placing it in the “very feasible” category. The mean score attained from the extensive evaluation of 33 eighth-grade students at Singkawang State Middle School 4 was 2550 out of a possible maximum score of 3036. The assessment categorized the score as “highly appropriate” for utilization as a learning tool.